The Oldest Possible Memory : Sammlung 1. - Meyer-Hermann, Eva; Sammlung Hauser und Wirth, St.Gallen (Köln : Oktagon Verlag, 2001)
Bourgeois, Louise ; Oppenheim, Meret ; Picabia, Francis ; Lucas, Sarah ; Balka, Miroslaw ; Broodthaers, Marcel ; Pettibon, Raymond ; Gordon, Douglas ; Rhoades, Jason ; Tillmans, Wolfgang ; Fischer, Urs ; Douglas, Stan ; Goldstein, Zvi ; Kawara, On ; Van Imschoot, Jan ; Absalon ; Schimert, Katy ; McCarthy, Paul ; Khedoori, Rachel ; Signer, Roman ; West, Franz ; Rist, Pipilotti ; De Keyser, Raoul ; Calder, Alexander ; Hyber, Fabrice ; Tuymans, Luc ; Gober, Robert ; Gonzalez-Torres, Felix
biog., bibliog. p. 84-86
Engels & Duits
The Oldest Possible Memory : Sammlung 1, Sammlung Hauser und Wirth in der Lokremise, St. Gallen, 14.05. - 15.10.2000
boek